Strategic Email Marketing for Customer Retention: A Study of E-Commerce Practices in Panai Hulu - NST, Ridho Ramdani; Hasibuan, Muhammad Irwansyah; Elvina, Elvina (International Journal of Economics Development Research (IJEDR), 2025)
This study aims to examine the influence of email marketing on e-commerce customer retention within the Panai Hulu Subdistrict, Labuhanbatu Regency. In the current digital era, email marketing has emerged as a key strategy for building and maintaining long-term customer relationships. The research employed a quantitative approach with an associative design, using questionnaires distributed to respondents who are active users of e-commerce platforms. The collected data were analyzed using SPSS software to explore the relationship between email marketing and customer retention. The results reveal that email marketing plays a significant role in enhancing customer retention, indicating that effective and well-targeted email strategies can strengthen customer loyalty. These findings highlight the importance of personalization and timely communication in email campaigns, suggesting that e-commerce businesses should optimize their email marketing practices to foster sustainable customer relationships and long-term business growth.